Pyrolysis of anaerobically digested and undigested sewage sludge: Comparative assessment of product quality, emissions, and carbon sequestration - Omar Moussa; Yassir Makkawi; Ondrej Masek; Baraa Mohamed (Energy Conversion and Management: X)
Anaerobic digestion is used for improved sludge treatment and biogas production; however, not all wastewater treatment plants incorporate it into their treatment train. This study provides a comparative assessment of anaerobically digested and undigested sludges to evaluate the impact of digestion on the downstream utilization of the sludge as a feedstock for pyrolysis. The digestion process yields a feedstock with lower volatiles and higher ash content (39.84 wt%), enhancing its mineral catalytic effect during pyrolysis. This leads to a lower bio-oil yield (max 15.2 wt%) but with higher calorific value (up to 36.96 MJ kg−1), reduced water content (max 16.68 wt%), and fewer oxygenated compounds. The increased catalytic activity also boosts the pyrolysis gas calorific value to 15.5 MJ kg−1, driven by a higher hydrogen yield (22.9 vol% at 650 °C). In contrast, undigested sludge yields more bio-oil and produces more chemically stable biochar with greater long-term carbon sequestration potential, especially when pyrolyzed above 450 °C. The biochar produced from both sludge types demonstrates good chemical stability, per the European Biochar Certificate guidelines, when produced at temperatures above 450 °C. It also contains acceptable levels of heavy metals, as specified by the International Biochar Standards, and has the potential to sequester approximately 31–47 Mt CO2e annually. The bio-oil shows potential to generate 110,808 GWh of global energy with significantly low emissions. Further research is needed to evaluate the economic and technical benefits of anaerobic digestion compared to the direct pyrolysis of undigested sludge.